2018
DOI: 10.18214/jkaem.2018.20.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Surface Electromyography and Conventional Electromyography in Facial Nerve Palsy

Abstract: Facial nerve palsy results from a dysfunction of cranial nerve VII (the facial nerve), which causes an inability to control facial muscles on the affected side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, it is significant that it can be used in clinical practice in conjunction with the theory of the Meridian muscle in Korean medicine [10]. Recently, studies on the assessment of facial nerve palsy using SEMG have also been reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is significant that it can be used in clinical practice in conjunction with the theory of the Meridian muscle in Korean medicine [10]. Recently, studies on the assessment of facial nerve palsy using SEMG have also been reported [11].…”
Section: Introductionmentioning
confidence: 99%